Antecedent Tourism Village as an Alternative Tourism Place during Pandemic - Hudiono, Rini (Budapest International Research and Critics University, 2022)
Tourism is one of the sectors most affected by the COVID-19 pandemic, considering that one of the instruments to suppress the increase in the number of cases is to limit human mobility. In order to restore tourism, several steps have been taken by the central government, through the Ministry of Tourism and Creative Economy. One of the educations to restart tourism is through the socialization of tourist villages. This research is a descriptive quantitative research, using probability sampling techniques to obtain 655 samples. Using multiple linear regression analysis, the results showed that travel distance, travel intensity, travel anxiety, and travel conditions on the tendency to travel in tourist villages obtained significant positive results. This means that the higher the respondent's perception of travel distance, travel intensity, travel anxiety, and travel conditions, the higher the tendency to travel in tourist villages, and vice versa.